GENDER AND AGE: LANGUAGE USE IN TV SERIES & THE IMPACT TO ENGLISH LEARNING - Marisa Fran Lina (State institute of islamic studies salatiga, 2019)
The purpose of the research is to find out the use of language in TV series in the perspective of gender and age. It is also found the differences and similarities among adult male, female and older people use the non-standard language. This research used a method of descriptive qualitative research, since it analyzes all the script on the TV series. The sample of the study is consisted of 2 parts which are divided into gender and age perspectives based on the underlying theories. The conversations were categorized as: two languages (Bahasa Indonesia or the original language of the TV series and English as the translation). The dialogs are also divided into standard language and non-standard language among adult males, females and older man (parents). Then, the findings of the research shows that Labov’s theory is rejected by Olive and Tara’s dialect in the dialog, but they support the statement of Aldous Huxley. Then, the utterances of Olive’s Father, it violates Downes’s theory who says that between the ages of 25 and 60 people choose standard as opposed to dialectical forms most frequently. Besides, by learning this journal, it is hoped that this article can be an example to the young generation early so that they do not participate in the decay of standard language specifically when they use in academic context.Keywords: Gender, Age, TV series, English Learning